THE ISLAMIC MODERATION : A Literature Review of the Concept Islamic Moderation according to KH. Ahmad Siddiq - M Muizzuddin (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
This study was intended to examine the Literature Study of the Moderate Islamic Concept according to KH. Ahmad Siddiq. Given that Islam is a religion of rahmatan lil Alamin, so Islam is considered capable of bringing peace in intolerant problems by far. In the analysis of this study, the researchers used the theory of Tri Ukhuwah by KH. Ahmad Siddiq, specifically Ukhuwah Islamiyah, Ukhuwah Wathoniyah, and Ukhuwah Basyariyah. This study was a qualitative study (literature study) with a philosophical approach. To obtain valid data and support this study, data were collected by researchers using the documentation method. The data were then analyzed by utilizing a deductive analysis technique, namely drawing conclusions based on general conditions. The results of this study illustrated that KH. Ahmad Siddiq is the central figure of NU who has succeeded in indicating the position between Islam and Pancasila. Besides that, KH Ahmad Siddiq also discussed the concept of brotherhood and moderate Islam with four interrelated components, including tawassuth (middle way), i’tidal (fairness), tawazzun (balance), and tasamuh (tolerance).